Acclimating Cucumber Plants to Blue Supplemental Light Promotes Growth in Full Sunlight - Chenqian Kang (Frontiers Media S.A., 2021)
Raising young plants is important for modern greenhouse production. Upon transfer from the raising to the production environment, young plants should maximize light use efficiency while minimizing deleterious effects associated with exposure to high light (HL) intensity. The light spectrum may be used to establish desired traits, but how plants acclimated to a given spectrum respond to HL intensity exposure is less well explored. Cucumber (Cucumis sativus) seedlings were grown in a greenhouse in low-intensity sunlight (control; ∼2.7 mol photons m–2 day–1) and were treated with white, red, blue, or green supplemental light (4.3 mol photons m–2 day–1) for 10 days. Photosynthetic capacity was highest in leaves treated with blue light, followed by white, red, and green, and was positively correlated with leaf thickness, nitrogen, and chlorophyll concentration. Acclimation to different spectra did not affect the rate of photosynthetic induction, but leaves grown under blue light showed faster induction and relaxation of non-photochemical quenching (NPQ) under alternating HL and LL intensity. Blue-light-acclimated leaves showed reduced photoinhibition after HL intensity exposure, as indicated by a high maximum quantum yield of photosystem II photochemistry (Fv/Fm). Although plants grown under different supplemental light spectra for 10 days had similar shoot biomass, blue-light-grown plants (B-grown plants) showed a more compact morphology with smaller leaf areas and shorter stems. However, after subsequent, week-long exposure to full sunlight (10.7 mol photons m–2 day–1), B-grown plants showed similar leaf area and 15% higher shoot biomass, compared to plants that had been acclimated to other spectra. The faster growth rate in blue-light-acclimated plants compared to other plants was mainly due to a higher photosynthetic capacity and highly regulated NPQ performance under intermittent high solar light. Acclimation to blue supplemental light can improve light use efficiency and diminish photoinhibition under high solar light exposure, which can benefit plant growth.